High-dose carbon-ion based radiotherapy of primary and recurrent sacrococcygeal chordomas: long-term clinical results of a single particle therapy center - Bostel, Tilman; Mattke, Matthias; Nicolay, Nils; Welzel, Thomas; Wollschläger, Daniel; Akbaba, Sati; Mayer, Arnulf; Sprave, Tetyana; Debus, Jürgen; Uhl, Matthias (Radiation oncology, 2020)
This study aimed to analyze the oncological long-term results and late toxicity of carbon ion-based radiotherapy (RT) of patients with sacral chordoma and to identify potential prognostic factors for local control (LC) and overall survival (OS).